Relaciones biométricas y proporción de sexos del cangrejo azul, Callinectes sapidus (Rathbun, 1896), en el Lago de Maracaibo, Venezuela. - Andrade de Pasquier, Glenys; García Pinto, Lope; Buonocore, Renzo; Méndez, Yaracelis (Ciencia, 2012)
Ver resumen pdf.